2013
DOI: 10.1051/0004-6361/201220755
|View full text |Cite
|
Sign up to set email alerts
|

CoRoT 102918586: aγDoradus pulsator in a short-period eccentric eclipsing binary

Abstract: Pulsating stars in eclipsing binary systems are powerful tools to test stellar models. Binarity enables us to constrain the pulsating component's physical parameters and this knowledge drastically improves the input physics for asteroseismic studies. The study of stellar oscillations then allows us to improve our understanding of stellar interiors and stellar evolution. The space mission CoRoT discovered several promising objects suitable for these studies. They were photometrically observed with unprecedented… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 55 publications
3
34
0
Order By: Relevance
“…This benefit was already demonstrated for the α Cen system (e.g., Miglio & Montalbán 2005) and for the above mentioned sdB pulsator PG 1336-018 (Van Grootel et al 2013) from ground-based asteroseismology and is being applied to space photometry now as well (e.g., Southworth et al 2011;Frandsen et al 2013, Maceroni et al 2013, Beck et al 2014Gaulme et al 2014;Boumier et al 2014). A recent overview of asteroseismology in eclipsing binaries with focus on solarlike pulsations is available in Huber (2014).…”
Section: Tidal Asteroseismologymentioning
confidence: 96%
“…This benefit was already demonstrated for the α Cen system (e.g., Miglio & Montalbán 2005) and for the above mentioned sdB pulsator PG 1336-018 (Van Grootel et al 2013) from ground-based asteroseismology and is being applied to space photometry now as well (e.g., Southworth et al 2011;Frandsen et al 2013, Maceroni et al 2013, Beck et al 2014Gaulme et al 2014;Boumier et al 2014). A recent overview of asteroseismology in eclipsing binaries with focus on solarlike pulsations is available in Huber (2014).…”
Section: Tidal Asteroseismologymentioning
confidence: 96%
“…Currently, only a few γ Dor pulsators in double-lined spectroscopic binaries are known, making their analysis very relevant for asteroseismology. Maceroni et al (2013) studied a γ Dor pulsator in an eccentric binary system, observed by CoRoT. Here, we are dealing with a non-eccentric system with a longer orbital period.…”
Section: Article Published By Edp Sciencesmentioning
confidence: 99%
“…In each step of the procedure, we used the entire Q1-Q10 dataset without any rebinning. Our iterative method is similar to the one described in Maceroni et al (2013) and consists of the following steps:…”
Section: Binary Modelmentioning
confidence: 99%
“…Even if the data analysis can be successfully accomplished, challenges are faced with the physical interpretation, particularly in the cases where tidally excited g-mode oscillations occur amidst (unidentified) free oscillations of (one of) the components in eccentric systems or when reflection effects are so strong that asymmetrically heated atmosphere models must be used before seismic interpretations can be attempted. Examples of eclipsing binaries with a mainsequence pulsator are, e.g., HD 174884 (Maceroni et al 2009), CoRoT 102918586 (Maceroni et al 2013), KIC 10661783 (Southworth et al 2012, Lehmann et al 2013, and KIC 4544587 (Hambleton et al 2013). The compact subdwarf pulsator 2M1938+4603 requires a new generation of atmosphere models before a solid interpretation can be made (Østensen et al 2010).…”
Section: Eclipsing Binaries: Complications and Opportuntiesmentioning
confidence: 99%